PROPHETIC INTELLIGENCE DALAM PERSPEKTIF PENDIDIKAN ISLAM - Suriadi Suriadi (STAI Sangatta Kutai Timur, 2022)
Islamic education is currently experiencing a decline, this can be seen in terms of the decline in human morals, both in educational institutions and in society. Intelligence has connectivity with the educational process as a concrete step in fostering human character as caliph fil ardh to think about all of Allah's creations. With this, the concept of prophetic intelligence provides a constructive and systematic space for delivering a good and comprehensive personality. Becoming a human being with good morals cannot be done instantly, through prophetic intelligence quoted from the Quran and al-Hadith, it is a must for the sustainability of conceptual Islamic education. According to this background, the problem that can be formulated is how is the relevance of prophetic intelligence to Islamic education today. While the aim is to find out the concept of prophetic intelligence, the relevance of prophetic intelligence to Islamic education today. The research method used is library research. The nature of the research is descriptive-analytic and the method of analysis is content analysis. The results of this study show that there are three concepts of prophetic intelligence, namely spiritual health that is free from nifaq, wickedness, and kufr as the basis for prophetic intelligence, Islamic principles by saying the creed, prayer, fasting, zakat, and hajj. The principles of faith, bermakrifat to Allah, the Angels, the Qur'an, the Prophet / Apostles, Doomsday, Qada, and Qadar. Prophetic Intelligence (Prophetic Intelligence) is very relevant in restoring existence and strengthening the foundation of the resilience of Islamic Education. With the concept of prophetic intelligence developed through spiritual health methods and planting aspects of humanization, liberation, and transcendence in Islamic education, it will help humans to have better personalities in accordance with the purpose of the Prophet Muhammad SAW revealed, namely to perfect human morals.